Pharmacokinetic Profiles of Active Ingredients and Its Metabolites Derived from Rikkunshito, a Ghrelin Enhancer, in Healthy Japanese Volunteers: A Cross-Over, Randomized Study - Kitagawa, Hiroyuki; Munekage, Masaya; Matsumoto, Takashi; Sadakane, Chiharu; Fukutake, Miwako; Aoki, Katsuyuki; Watanabe, Junko; Maemura, Kazuya; Hattori, Tomohisa; Kase, Yosio; Uezono, Yasuhito; Inui, Akio; et al. (PloS one, 2015)
Rikkunshito, a traditional Japanese (Kampo) medicine, has been used to treat upper gastrointestinal disorders such as functional dyspepsia and gastroesophageal reflux. This study investigated the exposure and pharmacokinetics of the ingredients of rikkunshito in healthy volunteers. First, an exploratory nonrandomized, open-label, one-period, noncrossover study using four healthy Japanese volunteers to detect 32 typical ingredients of rikkunshito in plasma and urine. As a result, 18 or 21 of 32 ingredients was detected in plasma or urine samples after oral administration of rikkunshito (7.5 g/day). Furthermore, a randomized, open-label, three-arm, three-period, crossover study using 21 subjects was conducted to determine the amounts of exposure and pharmacokinetic parameters of nine ingredients derived from rikkunshito (atractylodin, atractylodin carboxylic acid, pachymic acid, 3,3',4',5,6,7,8-heptamethoxyflavone, naringenin, nobiletin, liquiritigenin, isoliquiritigenin, and 18β-glycyrrhetinic acid) after oral administration of rikkunshito at three different doses (2.5, 5.0, or 7.5 g/day) during each period. The pharmacokinetic profiles of the nine ingredients in plasma were characterized. The geometric means (95% confidence interval) for the Cmax of the ingredients at a dose of 7.5 g were 1570 (1210-2040), 14,300 (12,200-16,800), 91.0 (71.8-115), 105 (75.6-144), 1150 (802-1650), 35.9 (24.6-52.5), 800 (672-952), 42.8 (30.4-60.3), and 55,600 (39,600-78,100) pg/mL, respectively, and for the AUC0-last were 1760 (1290-2390), 12700 (11,100-14,600), 1210 (882-1650), 225 (157-322), 4630 (2930-7320), 35.7 (20.4-62.7), 4040 (3260-5010), 122 (88.2-168), and 832,000 (628,000-1,100,000) pg·h/mL respectively. We identified the ingredients of rikkunshito that are absorbed in humans. Furthermore, we determined the pharmacokinetics of nine ingredients derived from rikkunshito. This information will be useful for elucidating the pharmacological effects of rikkunshito. Japan Pharmaceutical Information Center #CTI-121801 and -142522.